Performance analysis of coded multicarrier spread-spectrum systems in the presence of multipath fading and nonlinearities. - Je-Hong Jong (IEEE Transactions on communications)
In this paper, we analyze the effects of a nonlinear amplifier on the performance of convolutionally coded multicarrier spread-spectrum systems in the presence of multipath fading. Two performance measures, bit-error rate (BER) and adjacent channel power ratio (ACPR) are considered to assess the effects of in-band interference and out-of-band interference (spectral regrowth) from the nonlinear amplifier, respectively. A memoryless polynomial model is used to represent the bandpass amplifier amplitude nonlinearities (AM/AM) and a slow frequency-nonselective Rayleigh fading channel is assumed for each modulated carrier. Analytical results for the BER for uncoded systems and upper bounds on the BER for coded systems are presented. The optimum amplifier output power backoffs for both systems, which yield the smallest system power consumption, are also determined. The obtained ACPR shows its slow (inverse linear) falloff with the amplifier output backoff